Food and Feeding Habits of Bilih Fish Mystacoleucus padangensis (Bleeker, 1852) In Naborsahan River, Toba Lake, North Sumatera - Suryanti, Ani; Sulistiono, Sulistiono; Muchsin, Ismudi; Kartamihardja, Endi Setiadi (Journal Omni-Akuatika, 2017)
The bilih fish Mystacoleucus padangensis did a migration of the lake to the river that empties into the lake to spawn. This study aimed to determine whether migratory fish bilih ate when and what kind of natural foods consumed by bilih fish in it migration habitat. The study was conducted in Naborsahan River, Toba lake, North Sumatra. Sampling was done every 1 hour using Cast net. The results showed that bilih fish keep doing the feeding activity and having diurnal when migrated. The natural food bilih fish in the river and Toba lake was same, it was the phytoplankton of the class Bacilariopiceae. Natural food bilih fish that found in it intestine were phytoplankton include Rhizosolenia, Synedra, Gonatozygon, Closterium, Surirella, Pinnularia, Oscillatroria, Melosira, Gyrosigma, Aulacoseira and Zooplankton among others Creseis, Tubifex and Daphnia. The type of natural food that nostly found in bilih fish intestines were phytoplankton from the genus Synedra Bacilariopiceae with Index of Preporedance (IP) is 97.9 %. Based on the composition of the natural food that was dominated, bilih fish was categorized as the plankton feeder.